Influence of different universal adhesives on the repair performance of hybrid CAD-CAM materials - Gülbike Demirel; İsmail Hakkı Baltacıoğlu (Restorative Dentistry & Endodontics)
ObjectivesThe aim of this study was to investigate the microshear bond strength (μSBS) of different universal adhesive systems applied to hybrid computer-aided design/computer-aided manufacturing (CAD-CAM) restorative materials repaired with a composite resin.Materials and MethodsFour types of CAD-CAM hybrid block materials—Lava Ultimate (LA), Vita Enamic (VE), CeraSmart (CS), and Shofu Block HC (SH)—were used in this study, in combination with the following four adhesive protocols: 1) control: porcelain primer + total etch adhesive (CO), 2) Single Bond Universal (SB), 3) All Bond Universal (AB), and 4) Clearfil Universal Bond (CU). The μSBS of the composite resin (Clearfil Majesty Esthetic) was measured and the data were analyzed using two-way analysis of variance and the Tukey test, with the level of significance set at p < 0.05.ResultsThe CAD-CAM block type and block-adhesive combination had significant effects on the bond strength values (p < 0.05). Significant differences were found between the following pairs of groups: VE/CO and VE/AB, CS/CO and CS/AB, VE/CU and CS/CU, and VE/AB and CS/AB (p < 0.05).ConclusionsThe μSBS values were affected by hybrid block type. All tested universal adhesive treatments can be used as an alternative to the control treatment for repair, except the AB system on VE blocks (the VE/AB group). The μSBS values showed variation across different adhesive treatments on different hybrid CAD-CAM block types.